Lirikada vazn va qofiya uyg‘unligi (Bobur ruboiylari asosida) - Shafiqa Yarqin, Hamroyeva Orzigul Jalolovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The study of the creative and scientific heritage of Zahiriddin Muhammad Babur, a connoisseur of poetics, is one of the important tasks for literary studies. While creating a treatise on the science of poetics, Babur showed its practical results in his works. In particular, the practical application and artistic expression of the theory of aruz and rhyme are clearly visible in Babur's rubaiyats. Five types of rhyme related to weight and three special types, which are traditionally used in Turkish literature, are significant in Babur's work as an important factor indicating the literary environment of the time. In this respect, the analysis and research of poets' works is important. In the article, the rubai of the poet is analyzed, their aruz and rhyme possibilities are studied.